Synthesis of uniform Fe2O3@Y2O3 yolk−shell nanoreactors as chemical looping oxygen carriers - Fan, Qianwenhao (2024)
Iron-based materials are extensively employed as oxygen carriers in chemical looping processes, but their long-term performance is often inhibited by sintering and agglomeration. Here, we developed a yolk–shell structured Fe2O3@Y2O3 oxygen carrier, with each unit consisting of a Y2O3 shell encapsulating a nano-sized Fe2O3 core. The Y2O3 shell could protect the redox-active cores from sintering, and the void between the yolk and the shell is capable of tolerating cyclic volume and phase changes. During the simulated chemical looping cycles at 600 °C, the Fe2O3@Y2O3 oxygen carriers exhibit a consistent oxygen carrying capacity of 3 wt% over 50 cycles, without any distinguishable structural deterioration. With rational structure optimization, the Fe2O3@Y2O3 oxygen carriers with porous shell could enhance the mass transfer across the shell and enable higher reaction rates. The satisfactory sintering resistance of the Fe2O3@Y2O3 nanostructure demonstrates the feasibility of employing well defined yolk–shell structured oxygen carriers for chemical looping applications.